Optimization of ultrasound-assisted extraction based on response surface methodology using HPLC-DAD for the analysis of red clover (Trifolium pretense L.) isoflavones and its anti-inflammatory activities on LPS-induced 3D4/2 cell - Luo, Zhengqin; Xu, Yidan; Qiu, Longxin; Lv, Shiming; Zeng, Cheng; Tan, Aijuan; Ou, Deyuan; Song, Xuqin; Yang, Jian (Frontiers in Veterinary Science, 2023)
Introduction: Trifolium pratense L. has anti-inflammatory, antioxidant, cardiovascular disease prevention and estrogen-like effects. The existing method for the assay of effective components is commonly based on a spectrophotometer, which could not meet the requirement of quality control. Furthermore, although there have been many studies on the anti-inflammation effect of red clover, few have been reported on the regulatory effect of red clover isoflavones (RCI) on lipopolysaccharide (LPS) induced inflammatory response in porcine alveolar macrophages (3D4/2 cells) and its mechanism of action is still unclear. Methods: The main components of RCI including daidzein, genistein, and biochanin A were accurately quantified by high-performance liquid chromatography coupled with diode array detection (HPLC-DAD). after optimizing the extraction process through response surface methodology. The anti-inflammatory potential of RCI was carried out by detecting the level of inflammatory cytokines and mRNA expression of related genes. Further, its anti-inflammatory mechanism was explored by investigating two signaling pathways (NF-κB and MAPK). Results: The optimal extraction conditions of RCI were as follows: the concentration of ethanol is 86% and the solid-liquid ratio is 1:29, with the herb particle size of 40 mesh sieve. Under the optimal conditions, the total extraction of target components of RCI was 2641.469 μg/g. The RCI could significantly suppress the production and expression of many pro-inflammatory cytokines. The results of western blot revealed that RCI dramatically reduced the expression of p65, p-p65, IκB-α, p38and p-p38. These results are associated with the suppression the signal pathway of p38 MAPK, and to the contrary, activating the NF-κB pathway. Collectively, our data demonstrated that RCI reversed the transcription of inflammatory factors, and inhibited the expression of p65, p-p65, IκB-α, and p38, indicating that RCI had excellent anti-inflammatory properties through disturbing the activation of pathways of p38 MAPK and NF-κB. Conclusions: The extraction conditions of RCI were optimized by HPLC-DAD combined with response surface methodology, which will contribute to quality control of RCI. RCI had anti-inflammatory effects on the LPS-induced 3D4/2 cells. Its mechanism is to control the activation of NF-κB and p38 MAPK pathways, thereby reducing the expression of inflammatory related genes and suppressing the release of cytokines.